INFLUENTIAL DETERMINANTS OF THE INTENTION TO USE DIGITAL BANK - Gunawan, Vindi; Tjokrosaputro, Miharni (Graduate Program of Universitas Tarumanagara, 2024)
Lately, some traditional banking industries have opened their digital bank to fulfill world digitalization in many areas. This research was conducted to test the perceived usefulness and convenience of the intention to use digital banks mediated by attitude toward service. This research uses a quantitative research model with non-probability sampling techniques. This research will fill the gap in terms of study locations, which have different characteristics for each country, the subject of this research is the population of digital bank users in Indonesia, the sample collection technique. The results of this study show that Perceived usefulness has a positive but insignificant effect on intention to use. Furthermore, it shows that Attitude, Convenience, and Perceived Usefulness toward service positively and significantly affects intention to use. Additionally, Attitude toward service can mediate perceived usefulness and intention to use. This study shows that attitude toward service and convenience can increase the intention to use a digital bank. However, perceived usefulness cannot increase the intention to use a digital bank.